Lymphoproliferative disorders affecting organs of the head and neck - F. Sh. Kamolova; P. A. Zeynalova; R. I. Azizyan; A. A. Akhundov; I. A. Zaderenko; M. V. Bolotin; D. K. Stelmakh; V. I. Sokorutov; K. D. Ilkaev; V. T. Tsiklauri; Yu. V. Alymov; I. M. Gelfand; et al. (Опухоли головы и шеи, 2022)
Introduction. Lymphomas are a heterogenic group of tumors of the lymphatic and hematopoietic systems, and in many cases tumor process develops in the area of the head and neck including skin and mucosa, orbit, nasal cavity and paranasal sinuses, oral cavity, oropharynx, salivary glands, thyroid, and cervical lymph nodes. Differential diagnosis of lymphomas of the head and neck is complicated because it can be accompanied by another non-tumor pathology. High heterogeneity of lymphomas of the head and neck requires structurization of knowledge on their epidemiological and clinical manifestations.The study objective is to optimize early diagnosis as it allows to significantly increase cancer alertness in local practitioners, oncologists, diagnosis specialists and, in turn, to decrease verification frequency in generalized disease processes. Study of clinical characteristics of lymphoproliferative disorders of the head and neck leads to increased quality of differential diagnosis.Materials and methods. A study of lymphoproliferative disorders affecting head and neck was performed. Study material consisted of data on 174 patients hospitalized at the N.N. Blokhin National medical Research Center of Oncology between 1999 and 2020.Results. Based on the current clinical and morphological classification of lymphoproliferative disorders, data on location of lesions, characteristic signs of extranodal lesions and cervical lymph nodes involvement, as well as methods of diagnosis of lymphomas of the head and neck, are presented.Conclusion. The obtained data helps solve problems of diagnosis of lymphoproliferative disorders affecting the head and neck and serve as a basis for successful, predictable treatment of lymphomas.